1990
DOI: 10.4153/cmb-1990-037-0
|View full text |Cite
|
Sign up to set email alerts
|

On Number of Integers Representable as Sums of Unit Fractions

Abstract: Let N(n) be the set of all integers that can be written in the form where ∊(n) → 0 as n → ∞, answering a question of P. Erdös and R. L. Graham.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Concerning the lower bound of |N(n)|, Erdo s and Graham [1] asked whether |N(n)| =O(log n). This question was settled by the author [5]. He showed that |N(n)| ( 1 2 &=(n)) log n, where =(n) Ä 0 as n Ä .…”
Section: Introductionmentioning
confidence: 95%
“…Concerning the lower bound of |N(n)|, Erdo s and Graham [1] asked whether |N(n)| =O(log n). This question was settled by the author [5]. He showed that |N(n)| ( 1 2 &=(n)) log n, where =(n) Ä 0 as n Ä .…”
Section: Introductionmentioning
confidence: 95%
“…Concerning the order of |N(n)|, P. Erdo s and R. L. Graham [1] asked whether |N(n)| > >log n. This question was settled by the author [7]. He showed that \ 1 2 & log 2 n log n + log n |N(n)| log n+1.…”
Section: Introductionmentioning
confidence: 99%
“…where e k takes either 0 or 1: Answering questions of Erd + o os and Graham [5], we have shown (see [10][11][12][13]) that log n þ g À 2 À oð1Þ4jNðnÞj4log n þ g À 1 4 þ oð1Þ ðlog 2 nÞ 2 log n :…”
Section: Introductionmentioning
confidence: 99%